2000
DOI: 10.2337/diabetes.49.8.1347
|View full text |Cite
|
Sign up to set email alerts
|

Soluble leptin receptor in serum of subjects with complete resistance to leptin: relation to fat mass.

Abstract: Leptin resistance and obesity have been related to mutations of the leptin receptor gene in rodents and, recently, in a consanguineous family. The latter mutation results in a receptor lacking transmembrane and intracellular domains. Homozygous and heterozygous individuals with this mutation had serum leptin levels higher than expected, given their BMIs: 600, 670, and 526 ng/ml and 145, 362, 294, 240, and 212 ng/ml, respectively. Their serum leptin was fractionated by gel filtration: >80% was present as a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 26 publications
(28 reference statements)
9
55
1
2
Order By: Relevance
“…It has been suggested that the adipose tissue hormone leptin downregulates the secretion of its own binding protein 15,18 based on the findings that (1) leptin administration suppresses sOB-R levels in adults, 8 (2) a downregulation of leptin receptor isoforms by leptin has been demonstrated in vitro, 30,31 and (3) leptin receptor mutations are associated with high sOB-R levels. 32 In Table 2 Direct multiple linear analyses in 36 obese children with the dependent variables changes of leptin levels (Dleptin) in the 1-year period (r 2 ¼ 0.32), or changes of sOB-R (DsOB-R) in the 1-y period (r 2 ¼ 0.36), and the independent variables changes of weight status (DBMI) and changes of insulin resistance (DHOMA) adjusted for age, gender, and pubertal stage in each model Bold values were changed significantly related to the dependent variable in contrast to nonbold values. Table 3 Changes of BMI, SDS-BMI, leptin, sOB-R, insulin, glucose concentrations, and insulin resistance index (HOMA) over a 1-y period in 11 obese children (age in mean 9.472.0 y, 45% girls, 81% prepubertal) with substantial weight loss (decrease in SDS-BMI Z0.5) and in 11 age-, gender-and pubertal stage matched obese children without substantial weight loss (data as mean 7standard deviation; * ¼ Po0.05 baseline versus 1 y later) sOB-R in obese children T Reinehr et al contrast to this, leptin concentrations did not correlate to sOB-R levels at baseline, and most importantly, the changes of leptin levels did not correlate to the changes of sOB-R values in our study of obese children either.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the adipose tissue hormone leptin downregulates the secretion of its own binding protein 15,18 based on the findings that (1) leptin administration suppresses sOB-R levels in adults, 8 (2) a downregulation of leptin receptor isoforms by leptin has been demonstrated in vitro, 30,31 and (3) leptin receptor mutations are associated with high sOB-R levels. 32 In Table 2 Direct multiple linear analyses in 36 obese children with the dependent variables changes of leptin levels (Dleptin) in the 1-year period (r 2 ¼ 0.32), or changes of sOB-R (DsOB-R) in the 1-y period (r 2 ¼ 0.36), and the independent variables changes of weight status (DBMI) and changes of insulin resistance (DHOMA) adjusted for age, gender, and pubertal stage in each model Bold values were changed significantly related to the dependent variable in contrast to nonbold values. Table 3 Changes of BMI, SDS-BMI, leptin, sOB-R, insulin, glucose concentrations, and insulin resistance index (HOMA) over a 1-y period in 11 obese children (age in mean 9.472.0 y, 45% girls, 81% prepubertal) with substantial weight loss (decrease in SDS-BMI Z0.5) and in 11 age-, gender-and pubertal stage matched obese children without substantial weight loss (data as mean 7standard deviation; * ¼ Po0.05 baseline versus 1 y later) sOB-R in obese children T Reinehr et al contrast to this, leptin concentrations did not correlate to sOB-R levels at baseline, and most importantly, the changes of leptin levels did not correlate to the changes of sOB-R values in our study of obese children either.…”
Section: Discussionmentioning
confidence: 99%
“…14,32 Resistance to leptin is known to increase food intake, in extreme cases resulting in early-onset morbid obesity. 33,34 However, subjects homozygous for the 223Arg-encoding allele had a higher BMI than subjects homozygous for the common 223Gln-encoding allele in some, 14,35,36 but not all studies. 37,38 Again, long-term physiological adaptations required to facilitate homeostasis may be involved.…”
Section: Figurementioning
confidence: 93%
“…The very high circulating levels of leptin in the blood of these patients may mostly arise from a change in the half-life of the hormone due to its trapping by the soluble truncated receptor. 9 This result strongly argues for the absence of a direct feedback loop in the control of ob gene expression in human adipose tissue. This conclusion suggests that the concept of leptin resistance to explain the increased plasma concentration and mRNA levels of leptin in obesity may be not entirely relevant.…”
Section: Discussionmentioning
confidence: 89%
“…Circulating leptin levels were measured as reported. 9 Informed personal and parental consents were obtained and the local Ethic Committee (CCPPRB, Hôtel-Dieu, Paris) granted ethical permission.…”
Section: Patients and Protocolsmentioning
confidence: 99%
See 1 more Smart Citation